Communicate clearly - Heller, Robert (Essential managers., 1998)
Learn all you need to know about successful communication from interpreting body language to writing letters optimising meetings to speaking on the telephone. Communicate Clearly not only shows you how to hold an audience when making presentations and how to take notes or compile reports but also provides practical techniques for you to try in different settings. Power tips help you handle real-life situations and develop the first-class communication skills that are the key to a productive and informed workplace.